Determinants of Somatic Symptoms in Menopausal Women: The Role of Body Mass Index, Hemoglobin Levels, and Age - Sumarni Sumarni; Dyah Puji Astuti; Fitria Prabandari; Ossie Happinasari (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Background: Menopause is a physiological condition characterized by the permanent cessation of ovarian function and is often accompanied by somatic symptoms that may impair women's quality of life. Biological factors, including hemoglobin (Hb) levels, nutritional status, and age, may contribute to the occurrence of somatic symptoms among menopausal women. Objective: To analyze the association of hemoglobin levels, mid-upper arm circumference (MUAC), and age with somatic symptoms among menopausal women in Pasir Lor Village, Karanglewas District, Banyumas. Methods: This quantitative study employed an observational analytic design with a cross-sectional approach. A total of 67 menopausal women were recruited using total sampling. Hemoglobin levels were measured using a digital hemoglobinometer, MUAC was assessed using a measuring tape, age was obtained through interviews, and somatic symptoms were evaluated using the somatic domain of the Menopause Rating Scale (MRS). Data were analyzed using Spearman correlation and multiple linear regression tests. Results: The mean Hb level was 13.05±1.27 g/dL, MUAC was 26.97±3.38 cm, age was 54 (43–70) years, and the somatic symptom score was 3 (0–12). Hb (r=-0.341; p=0.005) and MUAC (r=-0.277; p=0.023) were significantly and negatively correlated with somatic symptoms. Age was not significantly associated with somatic symptoms (r=0.064; p=0.609). Multiple linear regression identified Hb as the most dominant factor associated with somatic symptoms (β=-0.290; p=0.016). Conclusion: Hemoglobin levels and MUAC were significantly associated with somatic symptoms among menopausal women, whereas age was not. Hemoglobin level was the strongest predictor of somatic symptoms.